Income Upgrading Model of Cattlemen in the Utilization of Artificial Insemination Technology: A Case Study in Village of Kanonang III, Regency of Minahasa - Wantasen, E; Hartono, B; Hanani, N (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2013)
Cattlemen allocate labor on their cattle business. These activities have contributed further to the family income used to meet household needs. Besides the beef business, they seek food crops such as rice, corn, peanuts and so forth to obtain additional income. The breeders utilize the technology of artificial insemination and natural mating in the beef cattle production. The usage of insemination technology is expected to increase the income derived from the beef cattle that will result in increasing the investments and the income of farming food crops. The objectives of this study are to analyze the correlating factors that affect the farmersâ income from the cattle business and farming crops under condition of the usage ofÂ artificial insemination technology andÂ to analyze the effects of the external factor changingÂ toward the profits ofÂ beef cattle business, the costs of cattle production , the cost of crop production,Â food crops farm income, animal health costs and the cost of the barn with the condition of the artificial technology usage. The measurement technology of the artificial insemination uses the cost inseminator approach. This research is a case study of 100 Â cattlemen in the village of Kanonang III Minahasa District selected by random sampling. Model of simultaneous equations with the method of 2 SLS is used to estimate all the parameters of the study. The result of research showed that the economic model of breeders can explain in relation to the use of artificial insemination with income and costs of production in cattleÂ and farm crops well. Insemination technology increases the profits for theÂ cattle production, the costs of cattle production,Â the costs of crop production, farm food crops income, animal health costs and the cost of the barn. These results indicate that the artificial insemination technology can improve economics the performance of beef breeders.Animal Production 15(2):144-152, May 2013